2019
DOI: 10.1007/s13744-019-00739-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Repellency Caused by Volatile Pyrethroids is Olfactory-Mediated in the German Cockroach Blattella germanica (Dictyoptera: Blattellidae)

Abstract: Pyrethroids are synthetic insecticides that have a repellent action. This effect has been associated with an increase in the locomotor activity, which causes the avoidance of the insecticide-treated area (excito-repellency). In this work, we studied with behavior and electrophysiological recordings the occurrence of olfactory-mediated repellency caused by pyrethroids of different volatility in the German cockroach Blattella germanica (Linnaeus, 1767). Male cockroaches were spatially repelled when they were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…found that d‐allethrin and vapothrin vapors spatially repelled German cockroaches while also increasing spontaneous neuronal activity. However, in the same study, permethrin neither spatially repelled nor increased spontaneous electrical activity in the German cockroach 46 . This study confirmed that the vapor pressure (and thus volatility) of pyrethroids plays a major role in determining repellency in German cockroaches.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…found that d‐allethrin and vapothrin vapors spatially repelled German cockroaches while also increasing spontaneous neuronal activity. However, in the same study, permethrin neither spatially repelled nor increased spontaneous electrical activity in the German cockroach 46 . This study confirmed that the vapor pressure (and thus volatility) of pyrethroids plays a major role in determining repellency in German cockroaches.…”
Section: Discussionsupporting
confidence: 63%
“…Although we tested several pyrethroids and pyrethroid-based products that are commonly used indoors, there are some pyrethroids that have low vapor pressure and high volatility which have been shown to possess true repellent (spatial) properties (e.g., transfluthrin, vapothrin, d-allethrin). [46][47][48][49][50] While much of this work has been done with mosquitoes, a recent study by Boné et al 46 found that d-allethrin and vapothrin vapors spatially repelled German cockroaches while also increasing spontaneous neuronal activity. However, in the same study, permethrin neither…”
Section: Discussionmentioning
confidence: 99%
“…Detection of EAG by bioallethrin is reminiscent of EAG elicited by d ‐allethrin and vapothrin (empenthrin) in the German cockroach 33 . Although it is not yet known if d ‐allethrin‐ or vapothrin‐mediated repellency is dependent on activation of Or(s), we found in this study that bioallethrin repellency is reduced in orco −/− mutant mosquitoes.…”
Section: Discussionmentioning
confidence: 56%
“…31 In addition, D-allethrin, containing four of the eight stereoisomers of allethrin, and vapothrin, another volatile pyrethroid (also known as empenthrin), have been reported to elicit electroantennogram (EAG) responses from the German cockroach (Blattella germanica). 33 These recent findings prompted us to address the following questions in this study: (i) can bioallethrin elicit non-contact repellency (i.e. spatial repellency) in Ae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation